Pengaruh Latihan Agility Terhadap Kemampuan Dribbling Sepak Bola Pemain SSB Koto Majidin Kabupaten Kerinci - Edo Yuliandra Pratama Edo Yuliandra Pratama (Indra Institute Research & Publication, 2021)
This study aims to see the effect of agility training on soccer dribbling ability at SSB Koto Majidin, Kerinci Regency. This type of research is Experimental. The population in this study were Kotomajidin football players, Kerinci Regency, totaling 40 people. The sampling technique was purvosive sampling, as many as 25 people. The data obtained is by doing a dribbling ability test. Data were analyzed using T test. Based on the results of hypothesis testing, it can be seen that tcount (9.174) > ttable (1.711). This means that the research hypothesis can be accepted. Thus, it can be concluded that agility training has a significant effect on dribbling ability. The increase in the dribbling ability of the SSB Kotomajidin ball in Kerinci Regency is 1.39 seconds, from an average score of 5.92 seconds in the pre test to 4.6 seconds in the post test.